Impulsive-compulsive behaviors are common in Asian Parkinson's disease patients: Assessment using the QUIP - Lim, Shen-Yang; Tan, Z.K.; Ngam, P.I.; Lor, T.L.; Mohamed, H.; Schee, J.P.; Tan, A.K.; Goh, J.Y.; Ooi, E.; Soh, P.Chin-Hooi (Elsevier, 2010)
Background: There are limited data on the prevalence of impulsive-compulsive behaviors and subsyndromal impulsive-compulsive behaviors in Asian patients with Parkinson's disease, who are treated with lower dosages of dopaminergic medications. Methods: The recently-validated Questionnaire for Impulsive-Compulsive Disorders in Parkinson's Disease was administered to 200 consecutive patients attending a Malaysian university-based neurology clinic. Informant report was also systematically obtained. Results: A high rate of Questionnaire positivity was found (35.0% by combined patient and informant report; 24.6% by patient report alone; 27.4% by informant report alone), despite usage of relatively low dosages of dopaminergic medications (mean/median total L-dopa equivalent units of 528/450 mg/day; mean/median agonist-only L-dopa equivalent units of 74/37 mg/day). Eating, sexual and punding or hobbyism behaviors were relatively common, while gambling and compulsive medication use occurred less frequently. Agreement between patient- and informant-reporting of impulsive-compulsive behaviors was moderate-to-fair (Kappa values ranging from 0.203 to 0.494). Factors associated with Questionnaire positivity on univariate analysis were male gender, younger age at Parkinson's disease onset, longer disease duration, use of dopamine agonist or amantadine therapy, higher total L-dopa equivalent units and higher dopamine agonist-only L-dopa equivalent units. On multivariate analysis, male gender and longer disease duration independently predicted Questionnaire positivity. No association was found with cognitive or apathy scores. Conclusions: Our findings suggest that Asian patients with Parkinson's disease may be susceptible to dopaminergic medication-related side effects. The data here also contribute to the understanding of the psychometric properties of the Questionnaire for Impulsive-Compulsive Disorders. (C) 2011 Elsevier Ltd. All rights reserved.